IMPACTOS DA CERTIFICAÇÃO ISO9001: UM ESTUDO EM EMPRESAS DO SETOR METAL-MECÂNICO DA REGIÃO FRONTEIRA NOROESTE DO RS - WAGNER, ADRIANO; SPAREMBERGER, ARIOSTO; SOARES, JULIO C. V.; FROEMMING, LURDES M. S.; GRAEF, NELINHO D. (Salão do Conhecimento, 2013)
Resumo